Pemberdayaan Masyarakat Desa Sidorejo dalam Menghadapi Pandemi Covid-19 di Era New Normal - Dimas Fanny Hebrasianto Permadi`; Anggita Mawar Sari; Belqis Nur Ivada Navalufi; Dika Dwi Kurniawan; Elisa Dwi Okta Sari; Endang Sri Rahayu; Fahrur Riska Ulinnuha; Imam Wahyudi; Ivanda Vipriyandhito; Khoirul Mujib; Melinda Sukma Ayu Adien Arera; Moh Aris Triprastya; Priadi Priadi; Riyonaldi Dwia Juang Saputra; Rofiatul Muzayyanah; Sri Lestari; Wahyu Setiawan; Yogi Prasetyo; Yordan Setyawan (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
Human life around the world is changing, including Indonesia, especially the people of Sidorejo Village. This change is due to the Covid-19 virus which forces people to adopt a new daily life. In this case, globally, people's social life must be able to adapt to new conditions. Human life everywhere enters a space called the New Normal. This article wants to explain how to implement the new adaptation of the Sidorejo Village community. A social condition of the community or individual behavior to prevent the transmission of the Covid-19 virus.